2020
DOI: 10.1093/gji/ggaa349
|View full text |Cite
|
Sign up to set email alerts
|

A complexity-driven framework for waveform tomography with discrete adjoints

Abstract: Summary We develop a new approach for computing Fréchet sensitivity kernels in full waveform inversion by using the discrete adjoint approach in addition to the widely used continuous adjoint approach for seismic waveform inversion. This method is particularly well suited for the forward solver AxiSEM3D, a combination of the spectral-element method (SEM) and a Fourier pseudo-spectral method, which allows for a sparse azimuthal wavefield parametrization adaptive to wavefield complexity, leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Even though the adjoint wavefield computed on the wavefield-adapted mesh has no intuitive interpretation, it still yields the correct misfit gradient. Along similar lines, Szenicer et al (2020) developed off-axis sources for AxiSEM3D which allows for adjoint computations within that framework.…”
Section: Adjoint Modellingmentioning
confidence: 99%
“…Even though the adjoint wavefield computed on the wavefield-adapted mesh has no intuitive interpretation, it still yields the correct misfit gradient. Along similar lines, Szenicer et al (2020) developed off-axis sources for AxiSEM3D which allows for adjoint computations within that framework.…”
Section: Adjoint Modellingmentioning
confidence: 99%
“…Testing for this specific threshold is beyond the scope of this study. We estimated the Fourier orders needed if we were to extend our 2.5D simulation to 3D based on Equation (5) in Szenicer et al (2020), and found 3D simulations are well out of reach given our available computational resources.…”
Section: Computational Methods and Its Enhancementsmentioning
confidence: 99%
“…• Szenicer et al (2020): A complexity-driven framework for waveform tomography with discrete adjoints.…”
Section: Literaturementioning
confidence: 99%